A cluster RCT and process evaluation of an implementation optimisation intervention to promote parental engagement enrolment and attendance in a childhood obesity prevention programme: results of the Optimising Family Engagement in HENRY (OFTEN) trial. - Bryant, Maria; Burton, Wendy; Collinson, Michelle; Farrin, Amanda; Nixon, Jane; Stevens, June; Roberts, Kim; Foy, Robbie; Rutter, Harry; Copsey, Bethan; Hartley, Suzanne; Tubeuf, Sandy; et al. (Trials, 2021)
Background: Poor and variable implementation of childhood obesity prevention programmes reduces their population impact and sustainability. We drew upon ethnographic work to develop a multi-level, theory-based implementation optimisation intervention. This intervention aimed to promote parental enrolment and attendance at HENRY (Health Exercise Nutrition for the Really Young), a UK community obesity prevention programme, by changing behaviours of children's centre and local authority stakeholders.Methods: We evaluated the effectiveness of the implementation optimisation intervention on HENRY programme enrolment and attendance over a 12-month implementation period in a cluster randomised controlled trial. We randomised 20 local government authorities (with 126 children's centres) to HENRY plus the implementation optimisation intervention or to HENRY alone. Primary outcomes were (1) the proportion of centres enrolling at least eight parents per programme and (2) the proportion of centres with a minimum of 75% of parents attending at least five of eight sessions per programme. Trial analyses adjusted for stratification factors (pre-randomisation implementation of HENRY, local authority size, deprivation) and allowed for cluster design. A parallel mixed-methods process evaluation used qualitative interviews and routine monitoring to explain trial results.Results: Neither primary outcome differed significantly between groups; 17.8% of intervention centres and 18.0% of control centres achieved the parent enrolment target (adjusted difference - 1.2%; 95% CI - 19.5%, 17.1%); 17.1% of intervention centres and 13.9% of control centres achieved the attendance target (adjusted difference 1.2%; 95% CI - 15.7%, 18.1%). Unexpectedly, the trial coincided with substantial national service restructuring, including centre closures and reduced funds. Some commissioning and management teams stopped or reduced delivery of both HENRY and the implementation optimisation intervention due to competing demands. Thus, at follow-up, HENRY programmes were delivered to approximately half the number of parents compared to baseline (n = 433 vs. 881).Conclusions: During a period in which services were reduced by external policies, this first definitive trial found no evidence of effectiveness for an implementation optimisation intervention promoting parent enrolment to and attendance at an obesity prevention programme.Trial Registration: ClinicalTrials.gov NCT02675699 . Registered on 4 February 2016.